Audyt informacyjnego systemu sieciowego - Kowalska, Marianna (Audit of the Network Information System, 2007)
The article is focused on audit of network information system. The main attention is concentrated on the audit issue as well as legal matters of its functionality. Additionaly, the paper contains also the audit procedure with all its important phases. The last part of the article presents standard audit documentation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 306-316